Cystic pancreatic lymphangioma - Gureş, Nazim (PAGEPress Publications, 2012)
Lymphangioma of the pancreas is a rare benign tumor of lymphatic origin. Retroperitoneal lymphangiomas account for 1% of all lymphangiomas. Herein, we report a case of cystic pancreatic lymphangioma diagnosed in 34 year-old female patient who was hospitalized for a slight pain in the epigastrium and vomiting. Radiological imaging revealed a large multiloculated cystic abdominal mass with enhancing septations involving the upper retroperitoneum. During the laparoscopic surgery, a well circumscribed polycystic tumor was completely excised preserving the pancreatic duct. The patient made a complete recovery and is disease-free 12 months postoperatively.